2018
DOI: 10.1007/s10461-018-2051-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Comorbidity, and Correlates of Psychiatric and Substance Use Disorders and Associations with HIV Risk Behaviors in a Multisite Cohort of Women Living with HIV

Abstract: We used the World Health Organization’s Composite International Diagnostic Interview to determine the prevalence, comorbidity, and correlates of lifetime and 12-month behavioral health disorders in a multisite cohort of 1027 women living with HIV in the United States. Most (82.6%) had one or more lifetime disorders including 34.2% with mood disorders, 61.6% with anxiety disorders, and 58.3% with substance use disorders. Over half (53.9%) had at least one 12-month disorder, including 22.1% with mood disorders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 77 publications
0
55
0
3
Order By: Relevance
“…WLWH also tend to engage in self-silencing, or not stating their needs in order to avoid relationship loss or abuse [ 28 ]. Self-silencing among WLWH has been associated with higher likelihood of depression [ 38 ], a lower likelihood of engaging in safe-sex behavior [ 29 ], and a lower likelihood of achieving ≥ 95% antiretroviral therapy (ART) adherence, especially among women who are racial/ethnic minorities or who have a history of abuse [ 30 ]. These multiple risk factors exist within the context of gender and racial inequities, and many researchers have called for interventions that specifically increase gender empowerment among WLWH to improve symptoms of depression, self-care and medication adherence [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…WLWH also tend to engage in self-silencing, or not stating their needs in order to avoid relationship loss or abuse [ 28 ]. Self-silencing among WLWH has been associated with higher likelihood of depression [ 38 ], a lower likelihood of engaging in safe-sex behavior [ 29 ], and a lower likelihood of achieving ≥ 95% antiretroviral therapy (ART) adherence, especially among women who are racial/ethnic minorities or who have a history of abuse [ 30 ]. These multiple risk factors exist within the context of gender and racial inequities, and many researchers have called for interventions that specifically increase gender empowerment among WLWH to improve symptoms of depression, self-care and medication adherence [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression remains the most common comorbidity for PLWH with rates as high as 34 to 67% among WLWH [ 37 ]. WLWH have higher rates of clinical depression than their uninfected peers, than the general population, and than MLWH [ 38 , 39 ]. Elevated depressive symptoms in WLWH are significant risk factors for worse self-care behaviors and heightened sexual risk behaviors [ 40 42 ] as well as for treatment non-adherence, virological failure (inability of anti-HIV drug treatment to reduce and maintain viral load to less than 200 copies per ml.…”
Section: Introductionmentioning
confidence: 99%
“…Here we examine whether associations between MDD and NCI differs between men and women as MDD is the most common neuropsychiatric complication among people with HIV (PWH) 11,12 and is more prevalent than in the general U.S. population [11][12][13][14] . The only nationally representative study among PWH reported an 18.5% 12-month prevalence of MDD 11,12 which is two-to three-times higher than the general U.S. population.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates in U.S. cohort studies are similarly high 14,15 . In the WIHS, current MDD via diagnostic interview was 20% and lifetime MDD was 32% versus 10% and 23% nationally 13 . In cognitive studies, about 30% of WIHS women report elevated depressive symptoms, [16][17][18] an estimate about 10% higher than other large-scale cohort studies of healthy midlife women [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Mental disorders can have a negative effect on the acceptance of treatment, development of high-risk behavior, and quality of life of these people [ 8]. In a study conducted by Cook et al (2018) study, the rate of anxiety disorders in positive HIV women in the United States was 61.6% [ 10]. Control and management of social phobia and exposure to stigma can have an important role in the treatment and care interventions of HIV positive patients.…”
mentioning
confidence: 99%